Preliminary study on mercury pollution affecting soil bacteria near a mercury mining area - Du, Jianxiong; Yuan, Yili; Li, Jianfeng; Zhang, Shuqing; Ren, Yuxiang (Frontiers in Microbiology, 2025)
In order to further explore the effect of mercury contamination soil (nearly 20 years) near a mercury mining area (Tongren, Guizhou, China) on the diversity and structure of the soil bacterial communities, five groups of soil samples (SMO2, SMO20, SMO30, SMO500, and SMO650) were collected at distances of 2, 20, 30, 500, and 650 m, respectively, from the only sewage outlet of a mercury mining area (Guizhou, China). All soil samples were collected from the 0–20 cm topsoil layer. After processing them, the soil microbial DNA was extracted from each soil sample, and sequenced via high-throughput sequencing technology. The sequencing results indicated a significantly greater diversity of the soil bacterial community in SMO2, SMO20, and SMO650 (relative high mercury contents) than in SMO300 and SMO500 (relative low mercury contents). Alpha diversity analysis revealed that the soil bacterial community diversity in SMO2 and SMO20 significantly exceeded that in SMO30, SMO500, and SMO650. The soil bacterial community structure analysis revealed identical and distinct dominant bacterial communities within the soil sample groups at both phylum and class levels. According to the further analyzed relationships between the soil environmental factors and bacterial community abundance for each sample group, the pH, distance (mercury content), and electrical conductivity (EC) had greater impacts on the structure of the soil bacterial community than available N, P, K. The survival of high relative abundance bacterial community taxa in the microbial communities provides compelling evidence of the high adaptability of bacteria to long-term mercury contamination of the soil environment. The results of this study provide a scientific reference and impetus for further research on the mechanism(s) responsible for tolerance to high mercury stress in mercury-contaminated soil.